Product Acquisition Management: An analytical Approach - LAI, YAN-LIN (2011)
The importance of closed loop supply chain is significantly increased in recent years due to the intensified competition, environmental protection and official obligation. Through recoverable manufacturing systems, not only the burden of environment can be reduced, but more important is that the systems provide great potential in profitability. However, the systems rely mainly on returned products as an essential input. Hence, from the perspective of product acquisition management, this research tries to explore the impacts of product return rates and quality level of returns on the profitability of the remanufacturing system through the development of optimisation models by an analytical approach with the consideration of financial incentives. The study also has shown the dependency of the optimal solutions on demand profiles, relevant costs such as cost of remanufacturing and incentive prices.